Factors Influencing Inter-Organizational Relations in The Industrial Market During a Coronavirus Pandemic - Dariusz NOWAK; Sebastian NAROJCZYK (Communications of International Proceedings, 2021)
The article attempts to identify and evaluate the factors influencing the creation, maintenance and development of inter-organizational relations in the MRO and OEM markets in the event of an epidemiological threat. In particular, efforts were made to find out which of them are of a priority nature, determining the quality and level of relationships in the context of high risk and high uncertainty. The conducted research was based on the traditional quantitative method, based on a comprehensive research questionnaire, addressed to a wide group of companies. It was enriched with a qualitative survey, including opinions, comments and conclusions of the respondents. The findings suggest that during the pandemic, the process of shaping and developing inter-organizational relations is influenced by eight cumulative factors with a relatively high cognitive load. In this group, it is possible to identify both those that take into account traditional aspects and those that played a much smaller role. In this group, the contractor's production capacity should be indicated as well as safety related to counteracting the spread of the pandemic.
Keywords: cooperation; Covid-19; inter-organizational relations; MRO and OEM markets; pandemic.